Incorporating play-based learning into early childhood education - Boxberger, Kimberly Sue (Kansas State University, 2023)
Children are naturally wired to do the very thing that will help them learn and grow. Play is a vehicle children use to explore surroundings, form critical thinking skills, and nurture emotions. The purpose of this study was to develop an understanding of how implementing play-based learning strategies would help social emotional behavior development and if there would be an improvement in literacy skills. The study examined connections between play, behaviors, and literacy by observing kindergarten students in a regular classroom setting. A variety of play-based learning stations were planned and utilized along with the incorporation of the mandatory curriculum to look for relationships in play, behavior, and literacy. Purposefully planned thematic units that included play-based learning were used during the study to investigate social-emotional learning and literacy skills. The methodology used in the study was action research which allowed me as the researcher to participate as needed to rotate actively as a participant, modeler, or facilitator. Using action research allowed for qualitative descriptions of behaviors to occur and looked for patterns in literacy skill development during play. Relying on literature reviews and educational theorists presented a foundation from which to build on and compare findings. The action research study reviewed the impact of implementing play-based strategies in a kindergarten classroom and in what ways it influenced social-emotional behaviors and literacy skills. Social-emotional behaviors and literacy skills are components of productive learning. Findings established that those observed in the study were affected in some fashion regarding both behaviors and literacy with the implementation of play-based learning strategies. Field notes, reflective journaling, and video recordings brought forth themes of engagement and creativity in the literacy skill portion of the study and themes of sharing, empathy, self-awareness, and collaboration in the behavior piece. These themes guided the study to determine if there were either positive or negative effects from either of two types of play-based learning, child-led or teacher directed. Child-led play allowed students to make free choices with same aged peers at stations, and teacher-directed play followed an objective with adult guidance at these stations. Both forms of play-based learning suggest changes in behaviors and literacy skills occurred. The findings indicate the need for an educational shift in the rigor curriculums use to a more developmentally appropriate practice. Educators should consider using play-based learning to make classroom practices exciting and shift to connecting real world problems to hands on learning.
Keywords: Play-based learning; Purposeful play; Early childhood education; Literacy; Social-emotional behaviors; Action research